2020
DOI: 10.2147/oarrr.s284555
|View full text |Cite
|
Sign up to set email alerts
|

<p>Knowledge, Awareness, and Perceptions of the Diagnosis and Management of Fibromyalgia Among Physical Therapists in Saudi Arabia: A Cross-Sectional Survey</p>

Abstract: Aim: To explore awareness of the diagnostic criteria and management of fibromyalgia (FM) among physical therapists practicing in Saudi Arabia. Methods: A cross-sectional survey was distributed electronically among musculoskeletal physical therapists. It was designed based on the research literature relevant to FM and reviewed by two rheumatologists for accuracy and comprehension. The survey included two sections: participants' demographic information and questions related to FM. The data were described using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 27 publications
4
19
0
Order By: Relevance
“…Knowledge and attitudes about FM among medical practitioners including physicians, nurses, and technologist/technicians in different regions of Saudi Arabia have been investigated, and the findings indicated poor knowledge about the diagnosis and treatment of FM (14). Another study from Saudi Arabia showed little awareness of or confidence in the assessment and management of patients with FM among physical therapists (10). In Egypt, Zeid and Ibrahim (15) have also recently shown a low knowledgeabout clinical presentation and treatment modalities of FM among Egyptian family physicians working in primary health care centers.…”
Section: Discussion:-mentioning
confidence: 99%
See 1 more Smart Citation
“…Knowledge and attitudes about FM among medical practitioners including physicians, nurses, and technologist/technicians in different regions of Saudi Arabia have been investigated, and the findings indicated poor knowledge about the diagnosis and treatment of FM (14). Another study from Saudi Arabia showed little awareness of or confidence in the assessment and management of patients with FM among physical therapists (10). In Egypt, Zeid and Ibrahim (15) have also recently shown a low knowledgeabout clinical presentation and treatment modalities of FM among Egyptian family physicians working in primary health care centers.…”
Section: Discussion:-mentioning
confidence: 99%
“…Studies assessing the awareness, perceptions, and attitudes related to the evidence-based diagnosis and management of FM have revealed large variations among healthcare providers including rheumatologists, general practitioners, and medical students, not only between different specialties but also within the same specialty (10).…”
Section: Introduction:-mentioning
confidence: 99%
“…In addition, no significant difference was shown between males (18.5%) and females (16.6%). Only awareness-level trials performed in Saudi Arabia were conducted among medical practitioners to investigate their ability to diagnose and manage FMS [ 29 , 30 ]. Also in other countries, the assessment of awareness and perception of FMS was set out among rheumatologists or among FMS Patients to explore the relationship between knowledge of HRQOL [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The FM-related questions were developed using the literature and FM-related studies as a foundation. [21][22][23][24][25]…”
Section: Instrument For Data Collectionmentioning
confidence: 99%